Inhibition of translation in living eukaryotic cells by an RNA G-quadruplex motif - Amit Arora; Mariola Dutkiewicz; Vinod Scaria; Manoj Hariharan; Souvik Maiti; Jens Kurreck (2008)
Guanine-rich sequences can adopt intramolecular four-stranded structures, called G-quadruplexes. These motifs have been intensively investigated on the DNA level, but their overall biological relevance remains elusive. Only recently has research concerning the function of G-quadruplexes in RNAs commenced. Here, we demonstrate for the first time, that an RNA G-quadruplex structure inhibits translation in vivo in eukaryotic cells. We investigated the function of a highly conserved, thermodynamically stable RNA G-quadruplex in the 5′-UTR of the mRNA of the human Zic-1 zinc-finger protein. Using dual luciferase reporter assay, we demonstrate that the Zic-1 RNA G-quadruplex represses protein synthesis inside eukaryotic cells. Quantitative RT-PCR assays confirmed that the reduction of protein synthesis is due to regulation of the translation process and not a consequence of reduced transcription. Western blot analysis revealed that expression of Zic-1 is strongly reduced by a 73 nucleotides-long fragment of the UTR containing the G-quadruplex motif. These structures might add to the more recently discovered elements in untranslated regions of mRNAs that regulate their translation.